Aplikasi Portable Brix Meter untuk Pengukuran Indeks Bias - Hidayanto, Eko; Rofiq, Abdul; Sugito, Heri (BERKALA FISIKA, 2010)
Measurement of concentration of sucrose (C12H22O11) solution using Portable Brix Meter was analized to determine its refractive index using Abbe refractometer. The materials used are sucrose solution with a concentration of 5%, 10%, 15%, 20%, 25%, 30%, 35% and 40%, and samples fruits of pear, watermelon, orange, apple and melon and others. The concentration of sucrose solution is proportional to the refractive index. The increase of concentration of sucrose solution will increase the refractive index. Correlation between the concentration of sucrose solution with refractive index is expressed by the equationÂ Refractive index of sucrose solution can be determined from its concentration. Keywords:Â sucrose solution, concentration, refractive index, portable brix meter